John Morreall und Tamara Sonn, The Religion Toolkit. A Complete Guide to Religious Studies - Schlosser, Dominik (Zeitschrift für junge Religionswissenschaft, 2014)
Rezensiertes Werk: John Morreall und Tamara Sonn. 2012. The Religion Toolkit. A Complete Guide to Religious Studies. Malden, Mass.: Wiley-Blackwell, New York, 2011, 344 S., ca. 25.90 €. ISBN: 978-1-4051-8246-1